Development of a condition‐specific patient‐reported outcome measure for measuring symptoms and appearance in vascular malformations: the OVAMA questionnaire. (1st October 2021) - Lokhorst, M.M.; Horbach, S.E.R.; Young‐Afat, D.A.; Stor, M.L.E.; Haverman, L.; Spuls, P.I.; van der Horst, C.M.A.M.
Summary: Background: The symptoms and appearance of vascular malformations can severely harm a patient's quality of life. The aim of treatment of vascular malformations generally is to improve condition‐specific symptoms and/or appearance. Therefore, it is highly important to start testing treatment effects in clinical studies from the patient's perspective. Objectives: To develop a patient‐reported outcome measure for measuring symptoms and appearance in patients with vascular malformations. Methods: A first draft of the patient‐reported outcome measure was based on the previously internationally developed core outcome set. The qualitative part of this study involved interviews with 14 patients, which led to a second draft. The second draft was field tested cross‐sectionally, after which groups of items were evaluated for adequate internal consistency (Cronbach's alpha > 0·7) to form composite scores. Construct validity was evaluated by testing 13 predefined hypotheses on known‐group differences. Results: The patient interviews ensured adequate content validity and resulted in a general symptom scale with six items, a head and neck symptom scale with eight items, and an appearance scale with nine items. Cronbach's alpha was adequate for two composite scores: a general symptom score (0·88) and an appearance score (0·85). Ten out of 13 hypotheses on known‐group differences were confirmed, confirming adequate construct validity. Conclusions: With the development of the OVAMA questionnaire, outcomes of patients with vascular malformations can now be evaluated from the patient's perspective. This may help improve the development of evidence‐based treatments and the overall care for patients with vascular malformations.